Mapping Research on Multimedia Biology: A Bibliometric Analysis - Yuyun Yuliani; Didit Ardianto; Rita Retnowati (Gemilang Maju Publikasi Ilmiah (GMPI), 2022)
The development of biology as a science and its application in technology that is increasingly rapidly encouraging innovative efforts to use technology results in biology learning. Currently, the biology learning process does not only use a single media but is required to use multimedia. This is done to make it easier for students to understand complex and very complex biological material. The aim of this paper is to provide an extensive bibliometric literature review on “multimedia biology education”. Articles found by Publishing or Perish software (PoP) with a Mendeley database. There are 200 articles found from the Google Scholar database from 2017 to 2021 which are analyzed in this study. The selected references are then managed using reference manager software, namely Mendeley. After managing the database, this research classifies and visualizes it using VOSviewer software. Overall, this review provides an appropriate reference point for further research on “multimedia biology education”. The search results 100 articles were obtained through the GS database and we found 55 articles were grouped from the GS database from 2017-2021 with the keyword 'biology education multimedia.This study aims to find research gaps for research on multimedia biology.